Research on the socialization of emotions in Latin American indigenous communities: challenges and opportunities - Jiménez-Balam, Deira (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
In psychological research on emotion socialization, a prevailing Eurocentric and Western perspective persists, conceptualizing emotions as individual and mental experiences, divorced from their relational and cultural nature. Latin America boasts significant cultural diversity; however, psychological studies in this field remain scarce. This article analyzes research on emotion socialization within Latin American indigenous communities. Reflections commence with a review of the limited research related to emotion socialization. Specifically, studies among the Maya of Mexico are emphasized to illustrate how the conception and socialization of emotions differ from the Eurocentric view. The necessity of an epistemic shift in studying emotions and their socialization is argued, both theoretically and methodologically. Additionally, emerging challenges and opportunities in studying emotions within Latin American indigenous communities are highlighted. Delving deeper into this field could contribute to a global understanding of emotional diversity across cultures and foster a Latin American psychology connected to communities, guiding the development of culturally relevant policies and interventions.